A novel photovoltaic emulator based on current-resistor model using binary search computation. (15th January 2018) - Ayop, Razman; Tan, Chee Wei
Highlights: A new PV emulator adapting resistance based PV model control strategy. Robust control strategy and quick computation of the PV emulator operating point. Highly accurate output performance for both resistive and MPPT load. Improved transient response up to 54% for the low output resistance. Abstract: The Photovoltaic (PV) emulator is a nonlinear power supply that produces a similar Current-Voltage characteristic of the PV module. This equipment simplifies the testing phase when developing the PV generation system such as the Maximum Power Point Tracking (MPPT) converter and PV inverter. However, the conventional control strategy used in the PV emulator, the Direct Referencing Method, is highly dependable on the parameters of the power converter circuit and the Proportional-Integral (PI) controller. As a result, the output voltage oscillates and becomes inaccurate at certain load conditions. In this paper, a new control strategy based on the Current-Resistance (I-R) PV model combined with the Binary Search Method is introduced. The I-R PV model is derived based on the single diode model. The closed-loop buck converter system with the current-mode controlled and the PI controller are used in the PV emulator system. The load of the PV emulator consists of the resistive load and the MPPT converter. The results obtained from the proposed control strategy are compared with the conventional Direct Referencing Method. The results show the proposed control strategy produces a more reliable operating point, a higher accuracy, and a faster transient response compared to the conventional Direct Referencing Method.